Novel dose–response analyses of treprostinil in pulmonary arterial hypertension and its effects on six‐minute walk distance and hospitalizations. (1st June 2020) - Ramani, Gautam; Cassady, Steven; Shen, Eric; Broderick, Meredith; Wasik, Allie; Sui, Qun; Nelsen, Andrew
Abstract : Treprostinil is a prostacyclin analogue approved for the treatment of pulmonary arterial hypertension. Apart from the inhaled formulation, there is neither a target dose nor a ceiling dose to guide clinicians using treprostinil; doses are individualized for each patient based upon tolerability and clinical improvement. Using combined data from the pivotal subcutaneous and oral treprostinil studies, we evaluated the effect of treprostinil dose on hospitalization and exercise capacity to better define the treprostinil dose–response relationship. Data from the pivotal subcutaneous and oral treprostinil studies were combined by converting oral doses to weight‐based continuous doses (ng/kg/min) accounting for patient weight and bioavailability. Patients were divided into dose tertiles (lowest, middle, highest 33%) and retrospectively analyzed. Analysis 1 assessed the effect of dose on pulmonary arterial hypertension‐related and all‐cause hospitalizations. Analysis 2 evaluated the effects of dose on six‐minute walk distance, Borg dyspnea score, and World Health Organization functional class. Results showed that, in Analysis 1, higher doses of treprostinil were associated with significantly longer times to first pulmonary arterial hypertension‐related and all‐cause hospitalization. In Analysis 2, there was a trend toward improvements in six‐minute walk distance with higher doses. In patients with pulmonary arterial hypertension on systemic treprostinil therapy, higher doses were associated with significantly longer time to first pulmonary arterial hypertension‐related and all‐cause hospitalization. There was a trend toward improvements in six‐minute walk distance. Collectively, these results underscore the importance of managing prostacyclin adverse events in order to achieve appropriate dose titration. Further studies are required to confirm these findings and to better characterize the dose–response relationship of treprostinil.